THE INFLUENCE OF PRICE, PRODUCT QUALITY, AND STORE ATMOSPHERE ON CONSUMER SATISFACTION AT HIMALAYAN COFFEE SHOP - Nurrisma, Medta; Djuwita, Diana; Saefulloh, Eef; Firdauzi, Indrawan (Cirebon International Journal of Economics and Business, 2025)
In Indonesia, coffee shops are developing very rapidly, starting to open in all corners of the country, from urban to rural areas. As a result, many coffee shop industries have emerged that offer a variety of coffee products. They also have a comfortable atmosphere and all the amenities needed to relax. The purpose of this research is to analyze the influence of price, product quality, and store atmosphere on consumer satisfaction at Himalayan coffee shops. This research uses a quantitative approach and association research with a sample of 100 Himalayan Coffee Visitors. The sampling technique is Purposive Sampling. Data collection techniques use observation, interviews and questionnaires. The power analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination test and hypothesis test with the help of SPSS 23 software. The research results from partial analysis show that price has a positive and significant effect on the consumer satisfaction variable, product quality has a positive and significant effect on consumer satisfaction, store atmosphere has a positive and significant effect on consumer satisfaction. Simultaneous calculation results show that Price (X1), Product Quality (X2) and Store Atmosphere (X3) have a positive and significant effect on Consumer Satisfaction (Y) of the Himalayan Coffee Shop.